Bilateral agreement for the period 2011/2013 LLP/Programme: higher education (Erasmus) between Universidade Lusíada de Lisboa and Wrocław University of Technology - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the LLP/programme. - Subject areas: Informatics, computer science.